The Effect Of Environmental, Social, And Governance Performance On Firm Value With Firm Size As A Moderating Variable - Jihan Arifah (Eduvest - Journal of Universal Studies, 2024)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) Performance on Firm Value with Company Size as a moderating variable in companies listed on the Indonesia Stock Exchange (IDX). This study uses an associative quantitative method with a sample consisting of 22 companies selected by purposive sampling from 2019 to 2021. The data was analyzed using multiple linear regression with classical assumption tests. The results showed that Environmental, Social, and Governance Performance had a positive and significant influence on Firm Value. Company size also acts as a moderating variable that strengthens the relationship between ESG Performance and Company Value. These results indicate the importance of implementing ESG principles to improve the competitiveness and sustainability of the company in the long term.